PERBANDINGAN PENGGUNAAN PELARUT ALKALI (KOH DAN NaOH) TERHADAP HASIL EKSTRAKSI RUMPUT LAUT MERAH (Eucheuma cottonii, sp) ASAL ACEH JAYA - Bhernama, Bhayu Gita (Department of Chemistry, Faculty of Science and Technology, UIN Ar-Raniry, 2019)
Indonesia is an archipelago that is rich in natural marine potential. One of the provinces in Indonesia that is rich in natural marine potential is Aceh. Aceh, which is rich in seaweed, has good prospects to improve the economy of its people. One of the seaweed cultivated in Aceh is Eucheuma cottonii, which has carrageenan content. In the process of carrageenan processing from seaweed alkali is needed which aims to produce carrageenan granules. Precipitation of carrageenan was carried out by heat extraction method which varied alkaline solvents namely NaOH and KOH and than do FTIR and SEM analysis. From the results of FTIR in the absorption area of ​​1010-1080 cm-1 showed the absorption of glycosidik bonds and at 849-850 cm-1 uptake was absorption from galactose-4-phosphate bonds. In wavelength is a type of carrageenan kappa. SEM results show different and uneven carrageenan surfaces.